Volatility of Exchange Rate and Export Growth in Pakistan: The Structure and Interdependence in Regional Markets (The Pakistan Development Review, 2004)
Pakistan follows the flexible exchange rate system since July 2000. Prior to this period it followed a managed floating exchange rate since 1982 and a fixed rate prior to 1982. Due to controlled exchange rate a little fluctuation in exchange rate was observed. It is empirical concluded that the Pakistan’s share of exports in world market did not indicate any significant change during fixed and managed floating exchange rate regimes [Kumar and Dhawan (1991)]. Pakistan’s share in world exports was stable during the last 24 years, ranging between a minimum of 0.12 percent in 1980 and a maximum of 0.18 percent in 1992. After introduction of floating exchange rate during 2002-2003 (the share was 0.17 percent) Pakistan’s exports performance was related to the volatility of exchange rate. Only one empirical study is available regarding to Pakistan’s context by Kumar and Dhawan (1991) who estimated the impact of exchange rate volatility on Pakistan exports to the developed world from 1974 to 1985. They found that volatility of exchange rate adversely effect on export demand. They also investigated the third country effect and suggested that Japan and West Germany act as the alternate market for Pakistan’s export to the United States and United Kingdom. The high degree of volatility and uncertainty of exchange movements observed in Pakistan is of great concern of policy-makers and researchers to investigate the nature and extent of the impact of such movements on Pakistan’s volume of trade. In many countries it is experienced that higher exchange rate volatility reduced the trade by creating uncertainty about future profit from exports.